2019
DOI: 10.1007/s11575-019-00401-x
|View full text |Cite
|
Sign up to set email alerts
|

How Inpatriates Internalize Corporate Values at Headquarters: The Role of Developmental Job Assignments and Psychosocial Mentoring

Abstract: Multinational companies (MNCs) often invite foreign subsidiary employees or inpatriates to their headquarters (HQ) to internalize the MNCs' corporate values and transfer those values to their subsidiaries after repatriation. However, there is a lack of understanding about how and why inpatriates internalize these corporate values during their HQ experiences. By integrating the perspectives of international adjustment and organizational socialization with that of on-the-job learning, we develop a model wherein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 100 publications
0
16
0
Order By: Relevance
“…Our study found that some developers helped the expatriates to overcome their uncertainties by providing them with emotional and psychological support during the assignment. It is in the lines of the psychosocial mentoring function where the expatriates are comforted by the developers by helping them cope with the stress associated with the novel work environments (Sekiguchi et al , 2019). The anchors also motivated the expatriates to develop networks and seek out job-related or other cross-cultural information.…”
Section: Resultsmentioning
confidence: 99%
“…Our study found that some developers helped the expatriates to overcome their uncertainties by providing them with emotional and psychological support during the assignment. It is in the lines of the psychosocial mentoring function where the expatriates are comforted by the developers by helping them cope with the stress associated with the novel work environments (Sekiguchi et al , 2019). The anchors also motivated the expatriates to develop networks and seek out job-related or other cross-cultural information.…”
Section: Resultsmentioning
confidence: 99%
“…Our research context is Asian MNCs in the Asian region. While early empirical studies on inpatriation offered insights based on data from European and American MNCs (e.g., Cerdin & Sharma, 2014;Harvey & Miceli, 1999;Reiche, 2006Reiche, , 2011, empirical efforts have recently expanded to Asia including Japan and Korea (Froese et al, 2016;Sarabi et al, 2017;Sekiguchi et al, 2019). Because of strong business growth and competitive pressures among global and local players in this region, there are increasing demands for MNCs to devise a more effective global staffing strategy to compete successfully in Asia (Budhwar & Debrah, 2009;Varma & Budhwar, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…More recently, Harzing et al (2016) show that expatriates and inpatriates are used to a similar extent: each subsidiary in their sample on average had 1.16 former inpatriates and 1.22 expatriates per 100 employees. There is also growing evidence that inpatriation is a useful means of disseminating and implementing HQ knowledge and shared corporate values throughout the MNC (Froese, Kim, & Eng, 2016;Moeller & Reiche, 2017;Sekiguchi, Takeuchi, Takeuchi, Nakamura, & Ebisuya, 2019). The increasing use of inpatriation might reflect the changed purpose of global staffing from top-down information processing to continuous knowledge creation in MNCs (Nonaka, 1994).…”
Section: Inpatriates As Knowledge Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inpatriates' intercultural mentoring (formal and informal, peer and hierarchical) is intended to promote international adjustment and new work assignment mastery. This intercultural mentoring also should address increased understanding and identification with the MNC's organizational culture and mindset that are typically felt most at headquarters (Sekiguchi et al. , 2019).…”
Section: Intercultural Mentoringmentioning
confidence: 99%